PENERAPAN PENDIDIKAN KARAKTER DISIPLIN TERHADAP SANTRI MADRASAH ALIYAH DI PONDOK PESANTREN MODERN AL-MA’ARIF - Elsa Nofita; Bambang Trisno; Yelvi Kurniati (ADIBA : JOURNAL OF EDUCATION, 2024)
This research is motivated by the importance of disciplined character for students because disciplined character forms a better person starting from the behavior, character and personality of students in carrying out the rules in the madrasah. Based on the phenomena that the author found, there are many students who do not follow the rules in madrasas, such as there are still many students who arrive late, students are late in participating in the learning process around 15 minutes to 30 minutes from the time the teacher enters the class and they are not allowed to enter the class and ask permission to picket teacher. The character of the santri lacks discipline who enters the class in groups when the pela lesson begins, where the santri do not respect the teacher when they are late and they are not afraid of the teacher, and do not listen to the teacher so that the santri do not obey school rules and abuse the teacher. This research uses a field research type of research, namely field research that is seen directly using qualitative descriptive methods as a procedure that produces data in the form of written or spoken words from people and behavior that can be observed in this research. The number of class XI students who will be studied 22 students. And data collection techniques are by observation and interviews. The key informants in this research were student representatives, and supporting informants were the boarding school leaders and class xi students at the Al-Ma'arif modern Islamic boarding school. The results of this research show that, the application of disciplined character education to Madrasah Aliyah students at the Al-Ma'arif Islamic Boarding School in Koto Selayan Bukittinggi. The boarding school leaders have included a disciplined character for the students and have established regulations and scheduled madrasas. Where in applying disciplinary character there is a method, namely looking at the objectives, materials and methods in applying disciplinary character. And also looking at the obstacles teachers have in implementing disciplinary character, one of the reasons we see is that students have different characters. The schedule for coming to school is to be at the madrasah at 7.00. and in Arsama it is also scheduled at what time to bathe, eat and so on and each has its own regulations and regulations. There are still students who are late for various reasons.